2023
DOI: 10.21203/rs.3.rs-2514206/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating anabolic-androgenic steroid dependence and muscle dysmorphia with network analysis

Abstract: Background Anabolic-androgenic steroid (AAS) dependence has numerous adverse health consequences, and may be driven in part by body image concerns, primarily muscle dysmorphia. This study aims to further understanding and identify potential clinical targets using network analyses of AAS dependence and muscle dysmorphia symptoms in males who used AAS and weightlifting controls. Methods A sample of 153 men who had used AAS and 88 weight-lifting controls were recruited through social media and relevant online f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Half of the women in our sample reported spending a signi cant amount of time on activities surrounding AAS use, while only two (14.3%) reported having experienced withdrawal symptoms. By comparison, we previously published ndings among male AAS using weightlifters where a similar proportion (41.7%) reported spending signi cant time on AAS, but a much larger proportion (50.4%) reported withdrawal symptoms (43). However, it is important to note that time spent includes many aspects of the lifestyle surrounding AAS use, including time training and managing diet and supplement use (27).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Half of the women in our sample reported spending a signi cant amount of time on activities surrounding AAS use, while only two (14.3%) reported having experienced withdrawal symptoms. By comparison, we previously published ndings among male AAS using weightlifters where a similar proportion (41.7%) reported spending signi cant time on AAS, but a much larger proportion (50.4%) reported withdrawal symptoms (43). However, it is important to note that time spent includes many aspects of the lifestyle surrounding AAS use, including time training and managing diet and supplement use (27).…”
Section: Discussionmentioning
confidence: 89%
“…However, it is important to note that time spent includes many aspects of the lifestyle surrounding AAS use, including time training and managing diet and supplement use (27). We have previously demonstrated that time spent may not be a central symptom in a network of AAS dependence symptoms (43). Sex differences in AAS dependence symptoms likely re ect sex-based differences in the experience of using AAS, where females may not experience as serious withdrawal due to lower endogenous testosterone.…”
Section: Discussionmentioning
confidence: 99%